An Islamic Legal Perspective on Inheritance Distribution in Panyangkalang Village, Takalar Regency - Sartika Sartika; Siti Walida Mustamin; Saidin Mansyur; Jasri Jasri; Alamsyah Alamsyah (Research in Education, Technology, and Multiculture, 2024)
Abstract: This research uses a qualitative method, namely describing the results of research findings related to procedures for dividing the inheritance of the Panyangkalang Village community based on a review of Islamic law. The results of the research show that the procedure for distributing community inheritance in Panyangkalang Village is carried out based on the traditions or customs of distributing the inheritance of their predecessors, that is, it is carried out evenly, whether the inheritance for men or women has the same amount. As for those who have more, the heir is the first person to take care of the heir either before or after he dies. So, the distribution of inheritance in Panyangkalang Village does not apply an inheritance distribution system based on Islamic law. This can be seen from the distribution procedure which is divided equally between men and women, there are inheritance disputes that occur which result in reporting to the Takalar Regency Religious Court.     Keywords: islamic law, inheritance distribution, qualitative research.